Neighborhood bully: no difference in territorial response toward neighbors or strangers in marmots. (4th July 2020) - Ferrandiz-Rovira, Mariona; Zidat, Timothée; Dupont, Pierre; Berger, Vérane; Rézouki, Célia; Cohas, Aurélie
Abstract: Territorial animals are expected to adjust their response to intruders according to the perceived threat level. One of the factors that drives threat level is the identity of the intruder. The dear enemy phenomenon theory postulates that individuals should respond with lower intensity to neighbors, already possessing a territory, than to strangers that may fight to evict them. In social species, the hierarchical status of the intruder might also mediate this response. Such behavioral adjustments presuppose a capacity to discriminate between individuals posing different threat levels. Here, we tested the behavioral response of Alpine marmots to territorial intrusions in a wild population. We compared both dominant females' and males' responses to scents from neighbor and stranger dominant males (dear enemy phenomenon) and to dominant and subordinate stranger males (social status-specific response). In addition, we tested for any covariance between male scents and social status. We showed that female and male dominant marmots do not adjust the intensity of their behavioral responses to whether the intruder's territory is bordering or not (neighbors or strangers) or to the intruder's social status, even though dominant and subordinate males are thought to pose different threats and social status is encoded in scents. Thus, we did not find support for the dear enemy phenomenon and conclude instead that, in dominant Alpine marmots, no intruder should enter a foreign territory. Research taking a more holistic approach of the evolution and maintenance of territoriality is required to understand the flexibility of responses to intruders in group-living species. Abstract : Territorial animals are expected to adjust their response to intruders according to the perceived level of threat. Depending on whether the intruder is a neighbor or a stranger or its social status, theory postulates that individual behavioral response to intruders should differ. However, alpine marmots do not respond more strongly toward neighbors or strangers nor toward dominant individuals or subordinates even though dominant individuals and subordinates pose different threats and social status is encoded in scent marks.